Hamlet: An authoritative text, intellectual backgrounds, extracts from the sources, essays in criticism - Shakespeare, William; Hoy, Cyrus (New York: W.W. Norton, 1992)
Based on the second quarto, with occasional reference to the folio, this work includes readings on melancholy, demonology, the nature of man and death, pre-Shakespearean accounts of the story of Hamlet and historical extracts. This edition offers the latest critical interpretations of "Hamlet".